The Effects of Training to the Employee Performance and Development: A Study of Fareast Islami Life Insurance Company Limited, Bangladesh - Hassan, Md. Shahinur; Mizanuzzaman, Md.; Islam, K. M. Anwarul (International Journal of Business and Management Future, 2020)
Fostering more efficient capital allocation; encouraging loss mitigation; enabling risk to be managed more efficiently; helping mobilized savings; facilitating trade and commerce; substituting for and complementing government security programs and promoting financial stability insurance company plays a vital role to a country's economy. Despite prolonged political instability, poor infrastructure, endemic corruption, insufficient power supplies, and slow implementation of economic reforms Bangladesh's economy has grown by approximately 6 percent annually for two decades. In this case, the insurance companies of Bangladesh have been keeping a significant role for a long since. Considering the enhancement of the development of insurance sectors, different institutes and academics have been established. But those are inadequate for the fulfillment of developing this industry and manpower also. So, regarding this context, I select the matter of The Effects of Training & Development of Performance: A Case Study of Fareast Islamic Life Insurance Ltd. This study is conducted to Fareast Islamic Life Insurance Head Office and its five branch offices. Identification of the improvement of manpower and their occupational development and how they can contribute to their organization is the main issue of this study.